The Application of Discussion Methods to Increase Student Learning Motivation in Fiqh Subjects in Class XI MA Al-Hasan Cikampek - Dede Irma Septiana; Imam Tabroni; Woolnough Cale; Mahon Nitin (Journal Emerging Technologies in Education, 2023)
Background. This study aims to determine the application of the discussion method to student learning motivation in fiqh subjects in class XI at MA AL-HASAN Cikampek. Purpose. the place of this research was carried out at MA AL-Hasan Cikampek. The main data source in this study is the XI class tutor in fiqh subjects, and students in class XI MA DI MA AL-HASAN Cikampek. Method. . This research is motivated by the interest and motivation of students in fiqh subjects that are very low, this can be seen from students who are indifferent during the teaching and learning process and do not pay attention when the teacher explains the subject matter. Results. . This happens because the teacher still uses the conventional method, namely the lecture method, thus causing students to become easily bored, and not focus on the teaching and learning process. To overcome this, it is necessary to apply a more innovative learning model, one of which is the discussion learning model. Conclusion. . The discussion learning model is a learning model that will shape the student's frame of mind through the discovery of ideas, ideas that can be discussed among fellow students, so that it will produce students who are active in thinking about the fiqh material discussed that day, thus student learning motivation will arise